The Caribbean in world affairs : the foreign policies of the English-speaking states - Braveboy-Wagner, Jacqueline Anne (Westview Press, Inc. BoulderUS, 1989)
Aims to fill the gap in the literature on foreign relations in the English-speaking Caribbean countries by integrating the known information into an analytical framework or model as first step toward theory building. Intends to reach the broader audience of those interested in small-state foreign policy, to facilitate comparisons with other countries of similar size.